Effect of ultrasonic treatment on the quality of Mianning ham - He, Jiaju; Wang, Wei; Zhang, Jiamin; Zhu, Yanli; Wang, Wenli; Bai, Ting; Ji, Lili; Chen, Lin (Frontiers in Nutrition, 2023)
This paper investigates the optimal process for ultrasonic desalination of Mianning ham. The study analyzed various factors such as ultrasonic treatment time, temperature, and power to determine their impact on the rate of desalination of hams. A single factor test was conducted to study the rate of desalination. Further, A Box-Behnken experimental design was used to evaluate the effect of Mianning ham desalination. The design examined the impacts of ultrasound on the physicochemical properties, texture, and sensory of the ham. Response surface processing group underwent oral processing to determine the optimal ultrasonic treatment conditions with the highest acceptance level. The results show that the best conditions were: ultrasonic time 84.56 minutes, ultrasonic temperature 40.35 ℃, and ultrasonic power 150.85 W. The average desalination rate of the ham under the optimal conditions was 25.93%±0.69%, and the hardness was 4.48 N±0.62 N. Overall, this process significantly improved the desalination rate, texture, and sensory quality of Mianning ham, providing solid theoretical support for desalination processing at the back end of ham.